Maternal birth preparedness and complication readiness in the Greater Accra region of Ghana: a cross-sectional study of two urban health facilities - Cynthia Klobodu; Brandy-Joe Milliron; Kofi Agyabeng; Patricia Akweongo; Augustine Adomah-Afari (BMC, 2020)
Abstract Background High maternal mortality ratios remain a critical public health concern in Ghana. Birth preparedness and complication readiness (BP/CR), which is a component of focused antenatal care, is a safe motherhood strategy intended to promote skilled birth attendance by helping women and their families plan for pregnancy and childbirth, thereby reducing maternal mortality. The objective of this study was to determine the level of BP/CR and to assess factors associated with maternal BP/CR in the Greater Accra Region of Ghana. Method A cross sectional descriptive quantitative study was carried out among 300 postnatal women attending the Adabraka Polyclinic and the Greater Accra Regional Hospital both within Accra, the capital city of Ghana. Data were collected with a structured questionnaire which assessed socio-demographic, health facility/provider and social support factors and their associations with BP/CR. Levels of BP/CR were assessed using validated tools. Data from 300 women were analyzed using STATA version 15.0. Logistic regression analysis was conducted to establish associations between BP/CR and socio-demographic, health facility/provider and social support factors. Results Approximately 234 (78%) of the women were birth prepared. Strong predictors of BP/CR included having ≥4 antenatal clinic visits (aOR 2.63; 95% CI 1.03-6.73), being employed (aOR 4.07; 95% CI 1.49-11.11) and belonging to maternal health promoting clubs or groups during the antenatal period (aOR 3.00; 95% CI 1.07-8.40) . Conclusion BP/CR is generally high among the study population. Predictors of BP/CR are multifactorial and found to cut across all aspects assessed in the study. Therefore, the creation of a BP/CR tool is recommended to routinely monitor trends in maternal birth preparedness in antenatal clinics. This may help to sustain and improve current levels and indicators of BP/CR.